2004
DOI: 10.1111/j.1467-9353.2003.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Commercial Hemp Production

Abstract: Hemp production has been nonexistent in the United States since the 1950s. However, low prices for traditional crops have peeked interest in commercial hemp production. The current literature on hemp suggests that it may compete on the margin with traditional crops, but is not likely to generate sizeable profits. Hemp appears slightly more profitable than traditional row crops, but less profitable than other specialty crops. An important constraint to a viable commercial hemp industry is the current state of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 1 publication
0
28
0
Order By: Relevance
“…Hemp seed is a small nut ovoid, with shiny surface uneven colour from brown to olive-coloured; depending upon the variety, the weight of one thousand seeds ranges from 20 to 23 g. Hemp seeds/ grains are smooth and about one-eighth to one-fourth of an inch long. Processing hemp seed involves hulling or pressing and crushing, depending upon the desired output [48]. Hemp seeds are mostly used for stock feed and, to a lesser extent, for oil.…”
Section: Post Harvesting Operationsmentioning
confidence: 99%
“…Hemp seed is a small nut ovoid, with shiny surface uneven colour from brown to olive-coloured; depending upon the variety, the weight of one thousand seeds ranges from 20 to 23 g. Hemp seeds/ grains are smooth and about one-eighth to one-fourth of an inch long. Processing hemp seed involves hulling or pressing and crushing, depending upon the desired output [48]. Hemp seeds are mostly used for stock feed and, to a lesser extent, for oil.…”
Section: Post Harvesting Operationsmentioning
confidence: 99%
“…Hemp has a long, storied past. It is considered one of the first cultivated crops in world history and was first commercially grown in the United States in the seventeenth century (Fortenbery and Bennett 2004). Hemp was crucial in the country's early years, but its production began to decrease in the late 1800s as innovations in cotton processing-such as the cotton ginmade hemp processing too expensive.…”
Section: Path Dependence In Hempmentioning
confidence: 99%
“…Fortenbery and Bennett [78] concluded that hemp is slightly more profitable than traditional grain crops, but less profitable than specialty crops, and on the whole is rather discouraging of future development. Robbins et al [79] examines the potential in Kentucky. Johnson [80] concluded that small scale, profitable niche markets for hemp products could make hemp an economically viable alternative crop for some regions of the USA.…”
Section: Economic Forecastsmentioning
confidence: 99%